2009
DOI: 10.1016/j.powtec.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Densification of rare-earth (Lu, Gd, Nd)-doped alumina nanopowders obtained by a sol–gel route under seeding

Abstract: Rare-earth (RE: Lu, Gd, Nd, 0.10 mol%)-doped alumina nanopowders were prepared by a new sol-gel route using polyhydroxoaluminum (PHA) and RECl3 solutions under -alumina (~75 nm) seeding. Among the rare-earth dopants studied, Lu yields the most suitable nanopowders for low-temperature densification. The 0.10 mol% Lu-doped nanopowders, which were obtained at a calcination temperature of 900°C under 5 mass% -alumina seeding, consisted of ~80-nm -alumina particles and -alumina nanoparticles. Using these Lu-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the present study, the microstructure of the transformed coatings retained a porous, vermicular structure for all the annealing temperatures studied. This is in contrast to the sintering studies of seeded gels 16–24 where the advantage of the seeding is the attainment of dense equiaxed structures at lower temperatures relative to unseeded samples. As put forward by Dynys and Halloran, 14 the vermicular structure is the result of the negative volume change from δ‐ to θ‐alumina, coupled with the constraint of the continuous transformation front.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In the present study, the microstructure of the transformed coatings retained a porous, vermicular structure for all the annealing temperatures studied. This is in contrast to the sintering studies of seeded gels 16–24 where the advantage of the seeding is the attainment of dense equiaxed structures at lower temperatures relative to unseeded samples. As put forward by Dynys and Halloran, 14 the vermicular structure is the result of the negative volume change from δ‐ to θ‐alumina, coupled with the constraint of the continuous transformation front.…”
Section: Resultsmentioning
confidence: 80%
“…It was the work of Messing and colleagues 16–18 that first showed that seeding bohemite gels with α‐alumina powder resulted in an enhancement of the transformation kinetics, and sintering of the transformed alumina could be achieved at a significantly lower temperature relative to the unseeded gels. This approach has since been widely applied to sol–gel‐derived aluminas for a broad range of applications 20–24 …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that properties of alumina influenced by trace impurities and additives [1,2]. The influence of rare earth oxides additions on the alumina properties was widely studied [3][4][5][6][7][8][9]. Odaka et al [9] reported that doping of Al2O3 with nanopowder rare earth oxides enhanced the densification at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of rare earth oxides additions on the alumina properties was widely studied [3][4][5][6][7][8][9]. Odaka et al [9] reported that doping of Al2O3 with nanopowder rare earth oxides enhanced the densification at low temperature. They claimed that the synergistic effect between the nano-sized alumina particles and suppression effect of the homogenously segregated rare earth dopant on the alumina grain growth are the reasons of the excellent low temperature densification of rare earth/alumina doped bodies.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Over the past decade, the synthesis of nanoparticles has been an important field of study in chemical science, and a significant contribution to manufacturing techniques of metallic colloids using metal salts as starting materials, such as sol-gels, 3,4 chemicals, 5 electrochemicals, 6 cellulose nanocrystal (CNXL), 7,8 and radiation-induced reduction. [9][10][11][12][13] In particular, radiationinduced synthesis is the most recent technology in this field, and is a promising method because of its many advantages and because of the "green" process achievable with irradiation techniques 14 compared to conventional methods: 1) radiation-induced synthesis is a clean process in which no chemical initiator or catalysts are used; 2) it is very simple and inexpensive; and 3) it is easily able to control the reduction of metal ion, and can be used to obtain metal nanoparticles that are fully reduced, very pure, and in a highly stable state.…”
Section: Introductionmentioning
confidence: 99%